Internalizing Democratic Educational Values in Learning Process - Ali Miftakhu Rosyad (International Journal of Science Education and Cultural Studies, 2024)
This research aims to analyze the internalization of democratic education values in education, more specifically regarding democratic values in education and the models used in instilling democratic education values. This research uses a systematic literature review method conducted by searching through reputable international journals related to democratic education values. This learning method provides the widest possible opportunity for students to express their opinions regarding the material presented by the teacher. Teachers teach students to be democratic, so that students are able to apply democratic values in their daily lives. The results show that the democratic values that are always successfully implemented are the values of tolerance, mutual respect and responsibility which are carried out through a process of habituation and instilling values. In future research, we link the values of democratic education in habits and understanding of values, so that the results of the research can be useful for the world of science.